Pemanfaatan Limbah Serbuk Kayu Karet Sebagai Olahan Baglog Media Tanam Jamur Tiram Untuk Meningkatkan Pendapatan Masyarakat - Irfandi Irfandi; Taufik Hidayat; Herkules Herkules; Izwar Lubis (Universitas Mathla'ul Anwar Banten, 2022)
UTILIZATION OF WASTE WASTE AS A PROCESSOR OF OYSTER MUSHROOM CULTIVATION MEDIA TO INCREASE COMMUNITY INCOME. The purpose of this service is to help the partners of the Nagori Dolok Maraja Oyster Mushroom Group Group in utilizing Rubber Tree Sawdust Waste by handling it properly so that it does not cause disease to the body and does not harm the natural ecosystem. The selection of this location is because in the village there are community groups who are entrepreneurs under the auspices of the Oyster Mushroom Business Group. In addition to having difficulties in developing their business. From the activities carried out, data was obtained on the training of making oyster mushroom Planting Media Baglog which was reviewed from various aspects, including: Selection of raw materials, the average participant got a score of 80 or entered the very good category, for the cleanliness of the tools the average participant got a score too very good, namely 83, while for the processing of waste products or baglog waste, the assessment obtained is quite low, namely 74 but still in the good category. For the neatness of product packaging, a general rating of 82 or very good was obtained and for product cleanliness it was also in the good category with a score of 79. The methods used to achieve the objectives of the activity were methods of education, counseling, production training, business management training, and mentoring. This activity was carried out in Nagori Dolok Maraja, Tapian Dolok District. Assistance and guidance starting from aspects, utilization of sawdust or rubber to become Baglog Media for Growing Oyster Mushrooms, production systems and business management so that it is expected to create economic independence and increase business income.